1981
DOI: 10.1021/jf00106a037
|View full text |Cite
|
Sign up to set email alerts
|

Protein-stabilized emulsions: effects of modification on the emulsifying activity of bovine serum albumin in a model system

Abstract: A series of laboratory blenders and homogenizers were compared for their capacity to make proteinstabilized emulsions. A Janke-Kunkel blender consistently gave the best emulsions. By use of optimum protein concentrations (0.5%) and temperature (15 °C), the effects of modification on the emulsifying activity (EA) of bovine serum albumin (BSA) over the pH range 2-10 were studied. Reduction of the disulfide bonds reduced the EA, urea (8 M)-eliminated EA, while succinylation significantly enhanced the EA of BSA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 13 publications
1
62
0
1
Order By: Relevance
“…The ability of discrete emulsion droplets to remain dispersed without creaming, flocculating, coalescing, or oiling off is defined as emulsifying stability (Waniska, Shetty, & Kinsella, 1981). The emulsifying stability index (ESI) values of SPI emulsions are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of discrete emulsion droplets to remain dispersed without creaming, flocculating, coalescing, or oiling off is defined as emulsifying stability (Waniska, Shetty, & Kinsella, 1981). The emulsifying stability index (ESI) values of SPI emulsions are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The oil droplet size distribution in the emulsion was assessed with the statistical diameter according to FERET using a light microscope at 600 x magnification WEB Carl Zeiss, Jena, GDR); for this purpose the emulsion is diluted 1 : lo00 with 0.05 % aqueous sodium dodecyl sulphate solution [6].…”
Section: Methodsmentioning
confidence: 99%
“…4), suggesting that the disulfide bonds play an important role in stabilizing the emulsion as well as the protein molecular weight. Waniska, Shetty, and Kinsella (1981) also reported that a reduction in disulfide bonds reduced the emulsifying activities (EA) of bovine serum albumin. When the sulphydryl groups in the proteins were chemically blocked, the emulsions that formed were less stable (Wu et al, 2011).…”
Section: Sds-pagementioning
confidence: 99%